SELECTION OF COFFEE PROGENIES WITH LARGE BEANS RESISTANT TO RUST AND CERCOSPORA LEAF SPOT - Pereira, Fernanda Aparecida Castro; Carvalho, Samuel Pereira de; Viana, Mariana Thereza Rodrigues; Vidal, Douglas Alves; Ferreira, Guilherme Souza; Silva, Joyce Alves Goulart da; Sâmia, Michelly Pereira (Coffee Science - ISSN 1984-3909, 2019)
Rust is the main disease of coffee. Recently, cercospora leaf spot has grown in importance, intensifying defoliation and decreasing grain yield. The aim of this study was to use a mixed model approach to select the best progenies of "Big Coffee VL" for resistance to rust and cercospora leaf spot. We used 12 progenies with high bean yields. Based on bean size, leaves and plant size, plants within each progeny were classified as "small" (P), "medium" (M) and "large" (G). The experimental design was completely randomized, with six replicates and one plant per plot. Six measurements were carried out every 15 days for each plant by selecting 20 fully exposed leaves with higher and lower sun exposures. The measurements summarized disease severity using two diagrammatic scales to obtain the area of the leaf under rust or Cercospora leaf spot. A mixed model approach was used to calculate genotypic value (GV) and heritability estimates. The Mulamba and Mock index was used to select the most resistant progenies, in which the sum of rankings was weighted by a heritability value. Five progenies were selected; three progenies were G (G17, G9, and G12), one progeny was M (M5) and another progeny P (P23). Among these, M5 and P23 progenies are the most productive and may have potential use in future studies. The statistical approach used to predict promising genotypes facilitates the selection of genetically superior individuals for maximizing yields.